General morphology and ultrastructure of the venom apparatus and convoluted gland of the fire ant, Solenopsis saevissima - Paterson Fox, Eduardo Goncalves [UNESP]; Bueno, Odair Correa [UNESP]; Yabuki, Antonio Teruyoshi [UNESP]; de Jesus, Carlos Massuretti [UNESP]; Solis, Daniel Russ [UNESP]; Rossi, Monica Lanzoni; Nogueira, Neusa de Lima (Univ Arizona, 2010)
A group of 13 species of the genus Solenopsis is markedly difficult to assess taxonomically, although they are of considerable economical and medical importance in some countries where some of them were introduced. These ants are aggressive and their venomous stings can be very allergenic. The venom apparatus has been described in fine detail for only two of these species, and differences in this structure among the different species might prove useful as taxonomic characters. The venom apparatus of Solenopsis saevissima Smith (Hymenoptera: Formicidae) is herein described with the aid of light and electron microscopy techniques, and compared to that of S. invicta and S. richteri. The cellular organization of the different parts present differences that suggest functional specialization. In general, the different tissues were abundant in vesiculae and mitochondria, but presented little endoplasmic reticulum and few ribosomes, probably because they produce little protein. The length of the free filaments of the venom gland and the width of their internal ducts seems to vary from what was described for S. richteri, but this may be of little use to taxonomy.
Keywords: Solenopsidini; internal anatomy; scanning electron microscopy; transmission electron microscopy